Importation, Mitigation, and Genomic Epidemiology of Candida auris at a Large Teaching Hospital. (6th December 2017) - Lesho, Emil P.; Bronstein, Melissa Z.; McGann, Patrick; Stam, Jason; Kwak, Yoon; Maybank, Rosslyn; McNamara, Jodi; Callahan, Megan; Campbell, Jean; Hinkle, Mary K.; Walsh, Edward E.
Abstract : OBJECTIVE: Candida auris (CA) is an emerging multidrug-resistant pathogen associated with increased mortality. The environment may play a role, but transmission dynamics remain poorly understood. We sought to limit environmental and patient CA contamination following a sustained unsuspected exposure. DESIGN: Quasi-experimental observation. SETTING: A 528-bed teaching hospital. PATIENTS: The index case patient and 17 collocated ward mates. INTERVENTION: Immediately after confirmation of CA in the bloodstream and urine of a patient admitted 6 days previously, active surveillance, enhanced transmission-based precautions, environmental cleaning with peracetic acid-hydrogen peroxide and ultraviolet light, and patient relocation were undertaken. Pre-existing agreements and foundational relationships among internal multidisciplinary teams and external partners were leveraged to bolster detection and mitigation efforts and to provide genomic epidemiology. RESULTS: Candida auris was isolated from 3 of 132 surface samples on days 8, 9, and 15 of ward occupancy, and from no patient samples (0 of 48). Environmental and patient isolates were genetically identical (4–8 single-nucleotide polymorphisms [SNPs]) and most closely related to the 2013 India CA-6684 strain ( 200 SNPs), supporting the epidemiological hypothesis that the source of environmental contamination was the index case patient, who probably acquired the South Asian strain from another New York hospital. All isolates contained a mutation associated with azole resistance (K163R) found in the India 2105 VPCI strain but not in CA-6684. The index patient remained colonized until death. No surfaces were CA-positive 1 month later. CONCLUSION: Compared to previous descriptions, CA dissemination was minimal. Immediate access to rapid CA diagnostics facilitates early containment strategies and outbreak investigations. Infect Control Hosp Epidemiol 2018;39:53–57